[OP.4A.11] THE TREATMENT BENEFIT OF THE ACE-INHIBITOR PERINDOPRIL ON TOP OF BETA-BLOCKER THERAPY IN PATIENTS WITH VASCULAR DISEASE AND HYPERTENSION. (September 2017) - Brugts, J.; Bertrand, M.; Remme, W.; Ferrari, R.; Fox, K.; Macmahon, S.; Chalmers, J.; Simoons, M.; Boersma, E.
Abstract : Objective: We aimed to determine the potential synergistic effect the combination of beta-blockers with perindopril in a hypertensive population with cardiovascular disease or at high a risk for cardiovascular disease. Design and method: In patients participating in the ADVANCE, EUROPA, and PROGRESS trials who were randomized to an ACE inhibitor based regimen or placebo, we identified all patients who received a beta-blocker at baseline. We considered patients defined as hypertensive in the original studies (>160/95 mmHg or use of antihypertensives). We studied the effect of beta-blocker and perindopril therapy on cardiovascular outcomes and mortality with a multivariate Cox regression analysis versus beta-blocker and placebo. Results: At baseline, 39% of patients in the three studies received a beta-blocker (n = 11418 out of 29 463 patients) and of these 51% were hypertensive (n = 5838). In the population receiving beta-blocker and perindopril, the composite end point of cardiovascular mortality, nonfatal myocardial infarction, and stroke was significantly reduced by 20% (HR 0.80, 95% CI: 0.71–0.90) compared with those receiving beta-blocker and placebo. The cardioprotective benefits seemed to be independent of the blood pressure effect. The reduction in risk of the composite endpoint by treating patients with beta-blocker/perindopril was 23% in patients with hypertension (HR 0.77, 95% CI: 0.66–0.89), and in non-hypertensive patients 16% (HR 0.84, 95% CI: 0.71–1.00), both significant without interaction. Within the hypertensive population, this significant benefit in the beta-blocker/perindopril group vs the beta-blocker placebo group was also observed for myocardial infarction (HR 0.74, 95% CI 0.58–0.94) and strong effect on all-cause mortality (HR, 0.68, 95% CI 0.57–0.82) (figure 1). Conclusions: The addition of perindopril to beta-blockers in hypertensive patients with vascular disease significantly improves survival and lowers the risk of myocardial infarction. Figure. No caption available.